What Hath God Wrought to Caesar: The Church as a Self-Interest Interest Group - Pfeffer, Leo (A journal of church and state, 1971)
Leo Pfeffer; What Hath God Wrought to Caesar: The Church as a Self-Interest Interest Group, Journal of Church and State, Volume 13, Issue 1, 1 January 1971, Pag